Natural Healing Methods as the Basis for the Development of Preventative Wellness Programmes – Arnold Rikli’s Potential - Grafenauer, Boža; Kužnik, Lea (The Business of Tourism, 2021)
Abstract This paper deals with the methods of natural healing that were practiced already in the 19th century by Swiss natural healer Arnold Rikli as a part of healing offer in Bled, Slovenia. The paper starts with the introduction of Rikli as a natural healer and his healing methods, based on hydrotherapy, heliotherapy, climate therapy and healthy diet. His healing methods were based on strengthening the immune system in a natural way. The paper takes an ethnographic approach based on in-depth analysis of the literature and online resources and fieldwork in Bled using the technique of partially structured interviews with the employees in tourist industry. The paper identifies the potential for the inclusion of Riklis natural healing methods in the modern tourist offer as the basis for creating Covid-adapted programmes and a source of survival for the existing wellness centres and other tourism providers in Bled.